3D Flow Structures During Upwelling Events in Lakes of Moderate Size. Issue 3 (21st March 2022) - Valbuena, Sergio A.; Bombardelli, Fabián A.; Cortés, Alicia; Largier, John L.; Roberts, Derek C.; Forrest, Alexander L.; Schladow, S. Geoffrey
Abstract: Upwelling can impact water quality dynamics in stratified water bodies. Conceptual models generally classify the upwelling response to winds in lakes into either a non‐rotational (2D, closed‐basin) model or a rotational (coastal upwelling) counterpart. The non‐rotational model is broadly applied in rotationally influenced lakes. The upwelling response to winds in stratified lakes may exhibit elements of both conceptual models. Here, we present the results of simulations with an accurate three‐dimensional numerical model of a lake of moderate size (Lake Tahoe, California–Nevada, USA), and focus our analyses on addressing the influence of the Coriolis force during the upwelling setup and relaxation phases. Upwelling was observed at the upwind boundary as well as along the coast to the left of the mean wind direction due to Ekman‐driven divergence. On the downwind shoreline, where downwelling occurs, alongshore currents appeared in response to wind forcing. Following the relaxation of the wind, our simulations reveal, for the first time, the existence of powerful cyclonic alongshore currents in lakes of moderate size, which are found to be in quasi‐geostrophic balance. These currents followed the characteristics of coastal jets often observed in large lakes and the coastal ocean. Our work leads us to conclude that upwelling setup in lakes with length scales ≈20 km and Burger numbers S < 1, exhibits a combination of dynamics predicted by both the non‐rotational, 2D, closed basin model, and the rotational coastal‐upwelling conceptual model. Key Points: Lakes of moderate size may exhibit upwelling at upwind shores and along‐wind shores due to the Coriolis force influence Upwelling dynamics in lakes of moderate size cannot be parameterized by applying a single conceptual model Cyclonic currents observed in Lake Tahoe are in quasi‐geostrophic balance and resemble coastal jets noticed in large lakes and coastal ocean